Measurement of S-parameters characterization using dielectric rod antenna / Mohammad Azrin Daud - Daud, Mohammad Azrin (2004)
The rectangular dielectric waveguide (RDWG) technique using dielectric rod antenna is one of a method for the determination of S-parameters and complex permittivity of wide class of dielectric materials of various thickness and cross-section. This project used the RDWG technique experiment setup together with TRL calibration method and Vector Network Analyzer (VNA) to measure S-parameters (S11 and S21) and complex permittivity of dielectric samples at X-band frequency (8- 12GHz). The dielectric antenna was designed and fabricated using 3D CAD programming. Measurement is compared with actual published value of material properties to demonstrate the benefit of RDWG technique. Measurement also compared with theoretical model based on microwave mathematical equations. The results of experiments almost close to theoretical data and further suggestion are presented to improve the technique.